The application of the Environmental Management System in the Business Wing of Civil Construction and the benefits of applying a Sustainable Development model (Research, Society and Development, 2022)
The objective of the present work is to analyze, in the light of a systematic review, the benefits of the operation of the Environmental Management System (EMS) in the field of civil construction in studies published in SPELL between 2014 and 2022. The results obtained indicate the benefits of adhering to a SGA, since there is a reduction in production costs, these resulting from the reuse of material in addition to saving time, without affecting the profits of the construction companies as well as the maintenance of the quality of the service. That said, it is demonstrated that this management method must be increasingly implemented and encouraged within the field of civil construction, aiming at improvements in performance, both operational and environmental.